PENGARUH KUALITAS LAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN NASABAH BANK TABUNGAN NEGARA CABANG KARAWANG - Nur Fitria Umar; Nuridin (Jurnal Manajemen Bisnis Krisnadwipayana, 2021)
To determine the effect of service quality and product quality on Customer Satisfaction at Bank Tabungan Negara, Karawang Branch. This research is included in the category of causal associative research using a quantitative approach. The population in this study were the customers of Bank Tabungan Negara, Karawang Branch, with the criteria being at least 17 years old, with a sample of 80 people with incidental sampling techniques. Methods of data analysis using partially and simultaneous linear regression. The results showed that partially or simultaneous service quality and product quality had a positive and significant effect on customer satisfaction at Bank Tabungan Negara, Karawang Branch.